Analisis Pengaruh Big Data Terhadap Pengambilan Keputusan Strategis Berbasis SIM - Widiya Wati; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study is to analyze the impact of big data on strategic decision-making based on Management Information Systems (SIM). In this digital era, data is one of the most important things for organizations. Data is one of the most important things for organizations. data provides big the ability to quickly and efficiently combine large amounts quickly and efficiently, thus allowing researchers to obtain more detailed information. Combining large amounts of information. Through qualitative research and content analysis of relevant literature, this study identified many ways big data can improve the effectiveness of strategic decision-making. All of this suggests that the integration of big data in a SIM can improve the accuracy and relevance of information used in decision development, which in turn can help organizations achieve success.